Thermal utilization of solar collector in substrate disinfestation - Santos, Ronaldo Antonio dos; Fraga Junior, Eusímio Felisbino; Andaló, Vanessa; Silva, Daniel Martins da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Disinfestation of the substrate is mandatory in the production of healthy and vigorous seedlings. However, conventional treatment with agrochemicals can be unsatisfactory, due to the costs and risks of biological vacuum and intoxication. To minimize these limitations, solarization emerges as a potentially viable technique. Therefore, this work evaluated the energy conversion of a solar collector and its capacity for disinfesting substrate with cricket (Gryllus assimilis (Fabr. 1775)). The equipment was built with a wooden box, with six galvanized steel tubes inside. The face of the box facing the sun had transparent glass, which allowed the entry of shortwave solar radiation and restricted the outflow of hot air masses. A completely randomized experimental design was used, with four solar radiation exposure treatments, each with five replications. During the experiment, it was found that the maximum temperature of the substrate was 70.4 °C, with a maximum thermal amplitude of 38.6 °C, between the interior and exterior of the equipment. The thermal variation, per unit of incident solar radiation, reached a maximum value of 1.61 °C.W-1.m-2. The quickest extermination of the insects occurred with two hours of exposure to solar radiation. The substrate temperatures inside the solar collector and the control, were on average 60.4 and 25.0 ºC, respectively.